Mineral and hormonal profile in acyclic and cyclic Murrah buffaloes during summer in Chhattisgarh - TIWARI, V P; TIWARI, R P; TIWARI, S P; KHAN, J R; POYAM, M R; AWASTHI, M K (The Indian Journal of Animal Sciences, 2012)
The experiment was conducted to study the incidence of cyclicity, biochemical profile (blood glucose, non esterified fatty acid (NEFA), macro minerals viz Ca, Pi, Mg, micro minerals viz Cu, Co, I, Zn, Mn, hormones, viz. progesterone and insulin in acyclic and cyclic Murrah buffaloes during summer (March to June 2009) in Chhattisgah. Out of 108 Murrah buffaloes 49 (45.37%) were found without palpable follicles and corpus luteum at per rectal examinations performed twice at 12 days apart, indicating true anestrus. The biochemical and hormonal profile were estimated in 6 cyclic and 24 acyclic Murrah buffaloes during summer. There was no significant difference in blood glucose and NEFA level in cyclic and acyclic buffaloes. The level of inorganic phosphorus and Mg were significantly lower in acyclic buffaloes than cyclic buffaloes. There was no significant difference in the level of calcium, however there was significant difference in Ca: P in cyclic and acyclic buffaloes. The micro minerals Zn, Fe, Cu, Co were significantly lower in acyclic buffaloes, however, there was no significant difference in the level of Mn and iodine. The serum progesterone level was significantly higher in cyclic than acyclic buffaloes. There was no significant difference in the level of insulin.